Upacara Tiwah Sebagai Daya Tarik Pariwisata di Kalimantan Tengah - Puspe, I Made (Dharma Duta, 2023)
Tourism is a field that is currently in great demand by various parties. Indonesia has great potential to generate foreign exchange from the tourism sector and the role of the national tourism sector is increasingly important in line with the developments and contributions made. The Tiwah Ceremony in Central Kalimantan is one of the tourist attractions. The Tiwah ceremony is a ceremony related to the ceremony after the human has died.